2009
DOI: 10.1111/j.1551-2916.2009.03287.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Strength of Polycrystalline Silicon Wafers for the Photovoltaic Industry

Abstract: The fracture strength of polycrystalline silicon wafers has been investigated by means of twist and four‐point bending tests. Under a twisting configuration, which generates high tensile stresses within the middle of the wafers, a unimodal distribution in strength is obtained. The characteristic strength and Weibull modulus are 131.0 MPa, and 14.4, respectively. Under a four‐point bending configuration, which generates high stresses both at the surface and at the edges, an additive bimodal distribution is obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 16 publications
0
22
1
4
Order By: Relevance
“…If edge chips or surface flaws arising from inadequate machining are the main factor to affect the strength, one may expect to see a deviation from the two-parameter Weibull distribution. 34 However, in our study, no significant deviation can be observed. Therefore, it is reasonable to assume that the extrinsic flaws introduced by machining are not the operative flaws controlling the strength.…”
Section: (4) Weibull Distribution Analysiscontrasting
confidence: 76%
See 1 more Smart Citation
“…If edge chips or surface flaws arising from inadequate machining are the main factor to affect the strength, one may expect to see a deviation from the two-parameter Weibull distribution. 34 However, in our study, no significant deviation can be observed. Therefore, it is reasonable to assume that the extrinsic flaws introduced by machining are not the operative flaws controlling the strength.…”
Section: (4) Weibull Distribution Analysiscontrasting
confidence: 76%
“…Moreover, the fact that the strength data can be fitted well using the two‐parameter Weibull distribution also indicates that machining flaws are unlikely to be the major reason to influence the strength. If edge chips or surface flaws arising from inadequate machining are the main factor to affect the strength, one may expect to see a deviation from the two‐parameter Weibull distribution . However, in our study, no significant deviation can be observed.…”
Section: Resultsmentioning
confidence: 91%
“…Consequently, it is essential to understand the fracture behavior of thin silicon wafers and to develop ways for their strength improvement. At room temperature, silicon is a brittle material and neither plastic deformation nor dislocation generation is observed when the applied stress exceeds a certain limit [3]. Its fracture strength is limited by the structural defects, which can serve as stress concentrators [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most studies focused their efforts on the impact of surface or edge damage, i.e., biaxial flexure test [7] is used to investigate the quality of the wafers surface, and four-point bending test [3] is applied to probe both surface and edges of the wafers. Moreover, fracture of brittle material exhibits statistical behavior and the Weibull analysis is applied to demonstrate the statistical fracture data [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Those wafer sawing processes, which can be regarded as a series of overlapping micro-indentations by sharp, abrasive particles, yield distinct damage pattern reaching tens of micrometers deep into the silicon surface, which are not completely removed by damage etching steps. [9][10][11] In the future, as the thickness of PV silicon wafer is reduced to 100 mm or less, wafer breakage issue due to the presence of micro-scale flaws will become even more detrimental. [9][10][11] In the future, as the thickness of PV silicon wafer is reduced to 100 mm or less, wafer breakage issue due to the presence of micro-scale flaws will become even more detrimental.…”
mentioning
confidence: 99%